Mental Health and Wellbeing training program for volunteers and professionals working with young asylum seekers who live in centers, shelters or refugee camps - Santos, Luisa Micaela Teixeira (2019)
PhD Project about about Mental Health and Wellbeing training program for volunteers and professionals working with young asylum seekers who live in centers, shelters or refugee camps